For a Performative Theatre in Pirandello: a brief dialogue with Deleuze and the theatre of repetition - Ribeiro (Fluminense Federal University, Niterói/RJ, Brazil), Martha de Mello (Revista Brasileira de Estudos da Presença, 2022)
This article is the result of practical research in the field of performing arts, with emphasis on processes and artistic achievements in studies focused in Pirandello’s scene studies. In search of a theatricality built from the intersection between theatre and performance, the dramaturgy of the Italian author is investigated from its head node: the acknowledgement by the playwright himself of the theatre’s unpower of representation. In this article, we organize documents and reflections derived from a year of practical activities around the Italian author’s scene and dramaturgy, revisited from a performative theatricality, in light of Deleuze’s concept of the theatre of repetition.